SUBKLİNİK MASTİTİSLİ İNEKLERDE KAN VE SÜTTE LİPİT PEROKSİDASYON VE BAZI ANTİOKSİDANLAR ÜZERİNE E VİTAMİNİNİN ETKİSİ - ŞİMŞEK, HALİL (Fırat Üniveristesi, 2002)
Bu araştırmada, subklinik mastitisli ineklerde E vitamininin lipit peroksidasyon ve bazı antioksidan düzeylerine etkisi araştırıldı. Araştırmada, 40 adet inek kullanıldı. Kontrol ve uygulama grupları, Kaliforniya Mastitis Testi (CMT) ve somatik hücre sayısı (SHS)'na göre belirlendi. Uygulama grubundaki ineklere 20 gün boyunca gün aşın 2.000 IU E vitamini kas içi uygulandı. Kontrol, uygulama öncesi ve sonrası gruplarında sırası ile sütte; SHS 169.60, 1.054.40, 700.80 (ml/süt), E vitamini 2.34, 2.04, 2.15 (mmol/L), Se 0.051, 0.045, 0.048 (ug/ml) ve MDA 0.50, 0.66, 0.58 (nmol/ml) olarak saptandı. Plazmada ise, E vitamini 5.79, 4.09, 5.11 (mmol/L), Se 0.099, 0.077, 0.081 (ug/ml) ve MDA 0.61, 0.75, 0.68 (nmol/ml) olarak bulundu. Aynı gruplarda sırası ile lökositte, GSH-Px 34.55, 22.02, 26.40 (IU/gr protein) ve MDA 111.67, 115.82, 113.47 (nmol/mg protein) olarak ölçüldü. Eritrositte ise, GSH 1.59, 1.35, 1.42 (umol/ml), GSH-Px 71.30, 54.90, 59.12 (IU/gr protein) ve Katalaz 52.19, 48.06, 50.32 (kU/gr protein) olarak saptandı. Kontrol grubu ile uygulama öncesi grup süt SHS, E vitamini ve MDA, plazma E vitamini, Se ve MDA, lökosit GSH-Px, eritrosit GSH, GSH-Px ve katalaz düzeyleri arasındaki fark istatistiksel olarak önemli bulundu. Süt Se ve lökosit MDA ortalamaları ise önemsiz bulundu. Uygulama öncesi ve sonrası gruplar arasında süt SHS ve MDA, plazma E vitamini ve MDA, lökosit GSH-Px, eritrosit GSH ve GSH- Px düzeyleri arasındaki fark istatistiksel olarak önemli bulundu. Süt E vitamini ve Se, plazma Se, lökosit MDA ve eritrosit katalaz ortalamaları farkının ise istatistiksel yönden önemsiz olduğu saptandı. Bu sonuçlara göre, subklinik mastitisli ineklerde E vitamini uygulamasının lipit peroksidasyonun önlenmesinde ve bazı antioksidanların aktivitelerinde olumlu bir etkiye sahip olduğu görüldü.

This study was carried out to determine the effects of vitamin E on lipid peroxidation and some antioxidant substances in subclinical mastitic dairy cows. Forty cows were assigned to two groups by California Mastitis Test (CMT) and somatic eel count (SCC). 2.000 IU vitamin E was injected to cows of treatment group by intramuscular route every other day for twenty days. SCC in milk samples of control group, pre-treatment and post-treatment was 169.60, 1.054.40, 700.80 (ml/milk), respectively. Vitamin E concentration of milk samples of control group and treatment group before and after treatment was 2.34, 2.04 and 2.15 (mmol/L) and Se levels were 0.051, 0.045, 0.048 (ug/ml) and MDA levels were 0.50, 0.66, 0.58 (mmol/ml), respectively. Plasma vitamin E, Se and MDA levels were 5.79, 4.09, 5.11 (mmol/L), 0.099, 0.077, 0.081 (ug/ml) and 0.61, 0.75, 0.68 (nmol/ml), respectively. Leucocyte GSH-Px and MDA levels with the same ordering of groups were 34.55, 22.02, 26.40 (IU/g protein) and 111.67, 115.82, 113.47 (nmol/mg protein), respectively. GSH, GSH-Px and Catalase levels in erytrocytes in control, before and after treatment groups were 1.59, 1.35, 1.42 (umol/ml), 71.30, 54.90, 59.12 (IU/g protein) and 52.19, 48.06, 50.32 (kU/g protein), respectively. Differences in milk SCC, vitamin E and MDA, plasma vitamin E, Se and MDA; leucocyte GSH-Px; erytrocyte GSH, GSH-Px and catalase levels between control and pre-treatment groups were significant changed while differences in milk Se and leucocyte MDA levels were not significant. In treatment group, differences between pre- and post-treatment in milk SCC and MDA, plasma vitamin E and MDA; leucocyte GSH-Px; erythrocyte GSH and GSH-Px levels were found as significant stastistically whereas differences in milk vitamin E and Se levels; plasma Se; leucocyte MDA and erythrocyte catalase activities were not stastistically significant. The results of the study indicate that vitamin E administration had a significant role in prevention of lipid peroxidation and positively influenced the activity of some antioxidants in subclinical mastitis cows.
The Effect of vitamin E on lipid peroxidation and some antioxidants in blood and milk of cows with subclinical mastitis
Keywords: Veteriner Hekimliği; Veterinary Medicine